Analysis of Advantages and Disadvantages of Current Operational Risk Management Models (AS/NZS 4360, AS/NZS ISO 9000, AS/NZS ISO 14000, AS/NZS 4801, AS/NZS 3806, AS/NZS 4444) - Ferry Jie; Hasan Akpolat; Deepak Sharma; James Irish (The Winners, 2002)
This paper will describe about the analysis of advantages and disadvantages of current operational risk management models (AS/NZS 4360: Risk Management, AS/NZS 4801: Occupational Health and Safety Management Systems, AS/NZS ISO 9001: Quality Management System, AS/NZS ISO 14001: Environment Management System, AS/NZS 3806: Compliance Management System, AS/NZS 4444: Information Security Management)  based on expert experiences and extracting the literature review. The advantages of most current models are widely adopted by industries of various of sizes as the basis for their operational risk management. In addition, they may help the organizations to improve the operations and competitiveness. However, there are some disadvantages of most current models such as the models are very general (guidance only), not specific to cover particular risks of industries.  And they don’t have the specific tools and processes.  In addition, they may not be able to integrate all elements of the management systems such as safety, health, environment, quality, security, and compliance.